POLITIK PENGGUNAAN BAHASA & LELUCON JAWA - J. Herudjati Purwoko, Ph.D. (Master Program in Linguistics, Diponegoro University, 2014)
This paper deals with a Javanese joke commonly used by Javanese parents to teach their young children a kind of typical cultural wisdom in accordance with their effort of socializing subsistence ethics. The respondents are all postgraduate students. Their age is roughly distinguished into two broad categories: (1) around 30 years, and (2) above 40 years. Most of those in the first category do not understand the essence of the joke at all, whereas all of those in the second category do remember and completely understand it. The reasons for their un/intelligibility become of paramount importance. Besides, the discourse of the typical joke also shows that a tiny piece of such a traditional product may reveal the process of meaning-making, in the study of language use, which is very “political” in characteristics. Makalah ini tentang lelucon Jawa yang digunakan oleh orangtua Jawa untuk mengajarkan kebijaksanaan khas kepada anak-anak sehubungan dengan usaha mereka dalam mensosialisasikan etika subsistensi. Para respondennya adalah mahasiswa pascasarjana. Usia mereka dibedakan dalam dua kategori: (1) sekitar 30 tahun, dan (2) di atas 40 tahun. Mereka yang dalam kategori satu tidak memahami esensi dari lelucon itu sama sekali, sementara yang dalam kategori dua mengingat dan memahaminya dengan baik. Alasan bagi mereka untuk tidak/memahami lelucon itu menjadi sangat penting. Di samping itu, wacana lelucon khas itu juga menunjukkan bahwa sebuah serpihan kecil dari produk tradisional semacam itu bisa mengungkap proses pembuatan-makna, dalam kajian penggunaan bahasa, yang bersifat sangat “politis”